2020
DOI: 10.5194/egusphere-egu2020-7520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine-learning inference of the interior structure of low-mass exoplanets

Abstract: <p>We explore the application of machine-learning, based on mixture density neural networks (MDNs), to the interior characterization of low-mass exoplanets up to 25 Earth masses constrained by mass, radius, and fluid Love number k<sub>2</sub>. MDNs are a special subset of neural networks, able to predict the parameters of a Gaussian mixture distribution instead of single output values, which enables them to learn and approximate probability distributions. With a datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…GJ 367b is more consistent with pure iron and an interior similar to Mercury. (B) The predicted relative thicknesses of each interior layer of GJ 367b from the neural network model (32). The core is assumed to be a liquid a Fe-FeS alloy.…”
Section: Figs S1 To S10mentioning
confidence: 99%
See 2 more Smart Citations
“…GJ 367b is more consistent with pure iron and an interior similar to Mercury. (B) The predicted relative thicknesses of each interior layer of GJ 367b from the neural network model (32). The core is assumed to be a liquid a Fe-FeS alloy.…”
Section: Figs S1 To S10mentioning
confidence: 99%
“…The effect of a different prior for the light gas layer (e.g. logarithmic sampling instead of linear), has minor effects on the resulting distributions, especially for the core and silicate layers (32), which dominate the interior structure of GJ 367b. The core and silicate layers use standard equations of state (EoS) (115), the ice layer is modelled using the EoS of water ice VII.…”
Section: Simultaneous Analysis Of the Tess Photometry And Harps Rv Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…These EoSs differ in whether or not they take temperature dependence into account. Baumeister et al (2018) performed an extensive parameter study to model the internal structure of a large number of subneptunian exoplanets of different compositions, ranging from super-Earths consisting only of a metallic core and silicate mantle to subneptunes with ice and gas layers. They found that for the rocky interior of an exoplanet, the choice of EoS has little effect on characterizing the planet's internal structure, and that for Earth-like planets, a simple isothermal EoS such as the third-order isothermal Birch-Murnaghan EoS is sufficient to accurately model their interiors.…”
Section: The Modelmentioning
confidence: 99%
“…Baumeister et al. (2020) used MDNs to predict the distribution of the possible interior structures of extrasolar planets for given mass and radius.…”
Section: Introductionmentioning
confidence: 99%